2007
DOI: 10.1007/s10620-006-9706-z
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection and Severity of Reflux-Induced Esophageal Disease in a Cohort of Patients with Columnar-Lined Esophagus

Abstract: The relationship between Helicobacter pylori infection and reflux-induced esophageal diseased is controversial. We examined esophageal disease severity in patients with columnar-lined esophagus and compared results between patients with and without Helicobacter pylori infection. Medical records of 1000 patients diagnosed with columnar-lined esophagus were examined. Endoscopic and histological findings of reflux-induced esophageal disease were compared between H. pylori-positive and H. pylori-negative patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Indeed, the prevalence of H. pylori was shown to be similar between GERD and other patients, and H. pylori was not related to the severity of GERD. [ 5 6 ] Recently, Japanese studies suggested that after H. pylori eradication, GERD symptoms are relieved, and life quality improved. [ 7 8 ] The Management of Helicobacter pylori Infection the Maastricht IV/Florence Consensus Report declares that H. pylori status has no effect on symptom severity, symptom recurrence and treatment efficacy in GERD.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the prevalence of H. pylori was shown to be similar between GERD and other patients, and H. pylori was not related to the severity of GERD. [ 5 6 ] Recently, Japanese studies suggested that after H. pylori eradication, GERD symptoms are relieved, and life quality improved. [ 7 8 ] The Management of Helicobacter pylori Infection the Maastricht IV/Florence Consensus Report declares that H. pylori status has no effect on symptom severity, symptom recurrence and treatment efficacy in GERD.…”
Section: Discussionmentioning
confidence: 99%
“…Low‐grade dysplasia has a threefold increased risk of progression to OAC compared with nondysplastic epithelium . No difference in severity of reflux‐induced esophageal disease was observed in BE patients with or without Helicobacter pylori infection …”
Section: How Does the Uk Barrett's Oesophagus Registry Operate?mentioning
confidence: 99%
“…reviewed 26 studies for evidence of an association between GERD and H. pylori infection and found a lower prevalence of infection in patients with GERD than in those without GERD 21 . While other studies have yielded similar results, 17,22–24 many have found no differences between H. pylori infection rates in patients with GERD and those in controls 25–29 …”
Section: The Epidemiological Evidence Of Gerd and The Absence Of H Pmentioning
confidence: 99%